Analysis of Factors Inhibiting First Grade Students' Beginning Reading - Jordi Andrea; Fitri Sakinah; Syahrul Ramadhan; Elifia Sukma (STAI Miftahul Ula Nganjuk, 2024)
Optimal conditions for beginning reading in grade I students are achieved when they have the ability to recognize letters, words, syllables and sentences, and are able to read fluently. However, the situation at SDN 20 Kurao Pagang shows that some grade I students experience difficulties in beginning reading. This study aims to analyze the factors inhibiting the ability to read beginning in grade I students of SDN Kurao Pagang, Nanggalo District, Padang City, in the 2022/2023 academic year, and describe alternative solutions to overcome these problems. The research method used was qualitative with a case study design. Data collection techniques involved observation, interviews, tests and documentation. The results showed that the factors inhibiting beginning reading in 8 grade I students of SDN 20 Kurao Pagang involved intellectual aspects, family environment, teaching methods at school, motivation from parents and self, student interest, student health, and online learning. Alternative solutions involved using appropriate learning methods, a variety of learning media, and special attention to students' needs. The conclusion from the results and discussion shows that the factors that hinder beginning reading include various aspects, and alternative solutions need to be implemented, such as the use of more diverse learning methods and media, as well as special attention to each student.